2022
DOI: 10.3390/su141912535
|View full text |Cite
|
Sign up to set email alerts
|

Study on Phosphorus Removal Pathway in Constructed Wetlands with Thermally Modified Sepiolite

Abstract: Constructed wetlands, as natural sewage treatment ecosystems, have been widely used in the fields of rural domestic sewage and sewage plant tailwater treatment. However, the synchronous removal of phosphorus in most constructed wetlands is not ideal. This study aimed to prepare thermally modified sepiolites with high phosphorus adsorption capacities and design a constructed wetland based on them. Thermal modification was adopted to enhance the adsorption capacity of sepiolite based on its high specific surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Sedimentation is often cited as the most important process for the retention of phosphorus in wetlands [44]. Other mechanisms include the adsorption of phosphorus by the substrate [45] and Puptake by macrophytes [46]. A systematic review of the efficiency of created and restored freshwater wetlands showed that the median removal rate of TP is 1.2 g m −2 year −1 , with a removal efficiency of 46%; both are significantly correlated with the inlet TP concentration, the hydraulic loading rate and the annual average air temperature [44].…”
Section: Sampled Water Quality Monitoringmentioning
confidence: 99%
“…Sedimentation is often cited as the most important process for the retention of phosphorus in wetlands [44]. Other mechanisms include the adsorption of phosphorus by the substrate [45] and Puptake by macrophytes [46]. A systematic review of the efficiency of created and restored freshwater wetlands showed that the median removal rate of TP is 1.2 g m −2 year −1 , with a removal efficiency of 46%; both are significantly correlated with the inlet TP concentration, the hydraulic loading rate and the annual average air temperature [44].…”
Section: Sampled Water Quality Monitoringmentioning
confidence: 99%
“…In general, the efficiency of phosphorus-removal in these systems is mostly dependent on several factors such as the nature of the substrate, environmental conditions, and plant species [53,57,92]. The major mechanisms for phosphorus-removal are natural sedimentation, precipitation, adsorption, and uptake by plants [108,112,115]. The precipitation process involves the conversion of dissolved phosphorus into a solid form that can settle to the bottom of the wetland, being later incorporated into sediment.…”
Section: Mechanisms Involved In Pollutant Removal From Domestic Waste...mentioning
confidence: 99%
“…The precipitation process involves the conversion of dissolved phosphorus into a solid form that can settle to the bottom of the wetland, being later incorporated into sediment. While adsorption plays a crucial role in phosphorusremoval, in the context of a VFCW system, phosphorus in wastewater can attach to the surfaces of substrate particles or plant roots, thereby reducing phosphorus concentrations in the treated water [53,115].…”
Section: Mechanisms Involved In Pollutant Removal From Domestic Waste...mentioning
confidence: 99%
“…Constructed wetlands mimic natural wetlands, purifying wastewater through an artificially designed structure that contains a substrate, aquatic plants, and microorganisms [15]. Depending on the engineering design and water flow pattern, constructed wetlands can be categorized into surface flow constructed wetlands (SFCW), horizontal subsurface flow constructed wetlands (HSSFCW), or vertical subsurface flow constructed wetlands (VSS-FCW) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%